Outcome of Pregnancy in Patients with Systemic Lupus Erythematosus - Erica Kwan Yue; Coriejati Rita; Laniyati Hamijoyo (Indonesian Rheumatology Association, 2017)
Background: Systemic lupus erythematosus (SLE) is an autoimmune disease which involves many different organ systems and immunological abnormalities. SLE mainly affects females in their reproductive age. This study aimed to describe the fetal outcome, neonatalcomplications, maternal outcome, and obstetrics complication in patients diagnosed with SLE, in order to help the physicians to reduce the fetal loss, improve maternal morbidity, and reduce neonatal or maternal deaths.Method: This research was conducted using descriptive quantitative design. Data were obtained from direct interview noted in a report form and medical records. Subjects were SLE patients who came to Rheumatology Outpatient clinic, Dr. Hasan Sadikin General Hospital, Bandung from September 2016 to November 2016; and fulfilled the inclusion and exclusion criteria. The minimal required sample was 96 subjects.Results: Due to time limitation, only 53 pregnancies from 40 females were managed to be recorded. The median age when being diagnosis of the subjects was 24 (14 - 41) years old. The fetal outcomes showed 64.2% live births, 18.9% spontaneous abortions, 9.4% intrauterine death, 1.8% intrauterine growth retardation, and 9.1% neonatal deaths. Neonatal complications included premature delivery, low birth weight, and growth retardation. Maternal complications during pregnancy included rash, pregnancy-inducedhypertension, arthritis, anemia, and thrombocytopenia. Furthermore, obstetric complications included 13.2% pre-eclampsia, 13.2% placenta previa, and 1.8% stroke.There were 2 cases (3.8%) of maternal death happened during the delivery.Conclusion: The most frequent maternal complications during pregnancy were arthritis and rash. Pre-eclampsia and placenta previa were the most frequent obstetric complications which experienced by the pregnant SLE patients. Exclude the live births, the most frequent fetal outcome was spontaneous abortion. The most frequent neonatal complications were preterm delivery and low birth weight.Keywords: pregnancy, systemic lupus erythematosus, fetal outcomes, maternal outcomes